Síntese de cristais líquidos discóticos não simétricos derivados do núcleo tris-[1,2,4]-triazolo-[1,3,5]triazina - Suassuna e Bega, Luis Augusto (2019)
In this work are described, the design, synthesis, characterization and some studies of the optical, thermal properties and supramolecular organization of the first asymmetric derivatives of tris-[1,2,4]-triazolo-[1,3,5]-triazine nucleus. Six asymmetric compounds were obtained by reaction of the cyanuric chloride with three strategically used different tetrazoles, which were prepared from commercial compounds following classical reactions of alkylation and 1,3-dipolar addition. All the final compounds had their formation confirmed by HRMS. However, the mixtures formed in the reactions were difficult to separate and only two compounds were isolated with high purity. The isolated compounds, TTT331 and TTT311, with asymmetric molecular structure, had their structures confirmed by 1H, 13C NMR. Only TTT331 had shown liquid-crystalline properties and had its thermal and mesomorphic properties investigated by MOLP, DSC and SAXS, the latter carried out at the National Synchrotron Light Laboratory. The analyzed compound presented Colh type mesophase over a wide temperature range (220.7 ° C, -21.7 ° C to 199.0 ° C), confirming a mesofase of great thermal stability when compared to other symmetric derivatives of the same tristriazolotriazine nucleus. In this way it was possible to make a systematic study comparing the molecular structure and its properties, showing that mesophase formation depends on the number of peripheral chains, for asymmetric derivatives of the nucleus studied. In addition, the loss of symmetry hinders the molecular organization necessary for the crystallization process by increasing the thermal stability of the mesophase, as observed for the asymmetric compound TTT331.